Consumption strikes back? measuring long-run risk - Hansen, Lars Peter 1952-; Latham, Anthony J. H. 1940-; Li, Nan (National Bureau of Economic Research, 2005)
"We characterize and measure a long-run risk return tradeoff for the valuation of financial cash flows that are exposed to fluctuations in macroeconomic growth. This tradeoff features components of financial cash flows that are only realized far into the future but are still reflected in current asset values. We use the recursive utility model with empirical inputs from vector autoregressions to quantify this relationship; and we study the long-run risk differences in aggregate securities and in portfolios constructed based on the ratio of book equity to market equity. Finally, we explore the resulting measurement challenges and the implied sensitivity to alternative specifications of stochastic growth"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Econometric models